Sikap Elit Politik Dalam Pemilihan Langsung Kepala Daerah Di Kota Manado - Kimbal, Alfon . (JURNAL ILMIAH SOCIETY, 2015)
Analyse of local political attitude elite to major election in Manado city depicting that positive attitude of Political Elite and also society and government to implementation of Pilkada in Manado City later. Some factor is assumed as impeller incidence of various problem at one particular area is : Collective Hardness and Mass Riot, Economics difference, political and social deprivasi, and primordialisme factor, like etnisitas and religion. There are seven strategic step in order to realizing implementation of Pilkada : Profesioalisme and Independency of KPUD, Role and Function of Parpol, Institute of Panwas, Role Of Self-Supporting Institute of Society (LSM), Reposition Role Of Government Officer Security, Role of Mass Media in Education of Politics, Sincerity and of siding Mass media. From three the finding hence can be concluded that 1)Positive attitude of Elite, Society and Government shall follow-up with existence of agreement between various side to realizing peaceful and peaceful Pilkada 2) the Various conflict that happened at area which will and have implementation of Pilkada have to anticipate early possible by approach among various side area and also always entangle society in every even and process of Pilkada as according to rule going into effect 3) Very expected by support and cooperation from various of side exist in area for the shake of its form of expectation with in the next Pilkada . Therefore suggested that by there is action of positive attitude of Local Elite to implementation of PILKADA Manado City.. In this case Elite becoming measuring rod in society have to really show of good Attitude in order to implementation of the next PILKADA because process of grab people conscience non by way of allowing all way for it